Outdoor farm, indoor farm - Metcalf, Lindsay H. (Astra Young Readers, an imprint of Astra Books for Young Readers, 2024)
Discover how both outdoor and indoor farms sustainably grow the food we eat throughout the year in this vibrant, rhyming picture book.